Ecological analysis of infectious diseases, healthcare access, and socioeconomic factors on stunting prevalence in West Sumatra Indonesia - El Zenitia Villa Rinjani; Dodik Briawan; Lilik Kustiyah (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Stunting is a condition of growth failure characterized by height below the expected standard for their age. The prevalence of stunting in West Sumatra has fluctuated above 20% between 2021 and 2023, highlighting its status as a public health issue. Unaddressed stunting in early childhood can adversely affect learning capacity and elevate the risk of non-communicable diseases later in life. This ecological study analyzes factors associated with stunting prevalence in West Sumatra using secondary data from 2021 sourced from the Health Office, Social Office, Central Bureau of Statistics, and the National Population and Family Planning Board across 19 districts/cities. The dependent variable was stunting prevalence, while the independent variables included acute respiratory infections (ARI), vitamin A supplementation, antenatal care (ANC), family planning, poverty, families at risk of stunting, and Conditional Cash Transfer (CCT) beneficiaries. Statistical analyses using Pearson and Spearman tests identified significant positive associations between stunting prevalence and ARI percentage (p=0,020), poverty level (p=0,023), and CCT beneficiaries (p=0,028). Conversely, ANC coverage showed a significant negative association with the prevalence of stunting (p=0,021). In conclusion, the prevalence of stunting in West Sumatra in 2021 is influenced by various factors, including ARI, poverty levels, PKH beneficiaries, and ANC coverage.